Effectiveness of Online Sexual Health Psychoeducation Program on Sexual Health Attitudes of Adolescents with Physical Disabilities: A Randomized Controlled Study. - Aşik, Raife; Karaca, Semra (Sexuality & Disability, 2024)
This study was conducted with the aim of meeting the sexual health needs specific to the development of positive sexual health attitudes that are ignored in adolescents with physical disabilities. In this study, a randomized experimental design was used to evaluate the effectiveness of the online sexual health psychoeducation program in adolescents with physical disabilities. The population of the study consisted of adolescents aged 12–15 who are members of The Spinal Cord Paralytics Association of Turkey (N:600). The sample size of the research was determined as 52 by power analysis and the analyzes were completed with 55 adolescents. When the effect of the online sexual health psychoeducation program given to adolescents with physical disabilities on sexual attitudes was examined, it was determined that the post-test and 3-month follow-up scores of the intervention group were higher than the pre-test scores. In other words, the adolescents with physical disabilities who participated in the sexual health education program had more positive attitudes toward sexuality, sexual behaviors, and sexually transmitted diseases than those who did not participate in the program, and these effects were sustained over three months. This study can be model for developing sexual health services to be offered to adolescents with physical disabilities. Trial Registration Number: NCT05732012. Registration Date: 08/02/2023.